UPAYA PENCEGAHAN PEREDARAN NARKOBA DALAM RANGKA MELINDUNGI MASYARAKAT DI KABUPATEN LOMBOK TENGAH NUSA TENGGARA BARAT - Muhammad Sood; Lalu Puttrawandi; Khairur Rizki (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Mataram, 2021)
This article is sourced from the results of community service in Central Lombok Regency in an effort to socialize the impact of drug trafficking, the causes of drug trafficking and efforts to prevent drug distribution in the community. The abuse of narcotics and dangerous drugs is a global phenomenon that is very frightening and dangerous for the nation and state. The bad effects of drug use have touched almost all levels of society at all levels, not only the general public, through the world of education from elementary school to college. Various effects of narcotics use include disrupting brain nerve cells, causing dehydration, hallucinations, chest pain, aggressive behavior, memory loss, causing seizures and death. Various factors cause the increase in the use of narcotics in society, such as personal factors in users due to a lack of understanding of religious teachings, family environmental factors such as broken communication between parents and children, social factors in society, especially with addicted friends. for drugs; factors of weak institutional roles, lack of guidance and outreach from the government and community leaders about the dangers of drug use, and weak law enforcement. Various efforts can be made to prevent the entry and circulation of narcotics and illicit drugs in West Nusa Tenggara, both through preventive efforts such as socialization, guidance and supervision, as well as the imposition of repressive measures, such as the application of criminal sanctions for drug dealers.